A First Look at the Science-Policy Interface for Ocean Governance in the Wider Caribbean Region - McConney, Patrick; Fanning, Lucia; Mahon, Robin; Simmons, Bertha (Frontiers in Marine Science, 2016)
Weak governance is a root cause of the problems constraining the sustainable management of shared living marine resources within the Wider Caribbean Region (WCR). Integral to any fully functioning policy cycle in governance is the communication of marine science data and information, through the stages of the policy cycle, ultimately for use in decision-making. The networks of ties between science and policy constitute science-policy interfaces. Connecting science to policy is a major issue confronting the world today in efforts to achieve sustainable development. In order to develop a regional science-policy interface for ocean governance in the WCR we must first understand what currently exists. In this paper we describe the process and product of an interview investigation of the marine science-policy interface in the WCR. Policy discussions that used marine science extensively were infrequent. Constraints on use of science included low capacity, science not being provided in policy-relevant format, not having easy access to databases and low policy demand for science. There is little transboundary marine science information sharing except through informal social networks. The absence of a culture of evidence-based policy-making in the region must be addressed before there will be any significant change in use of properly packaged marine science. External influences, political context, science and evidence, links and networks are used to systematize the key learning.